IMPLEMENTASI TANQIH AL-MANATH DALAM PENERAPAN HUKUM - Meirison, Meirison (JURNAL NIZHAM, 2014)
Praise be to Allah, the Lord of many good and blessed as our Lord loves and which pleases him, praise report to grace, and rewards the more tender, and peace and blessings be upon the Prophet and Apostle Selected by The God and his family and peace much. After:The science of jurisprudence of science mission that indispensable research in the science of law, as the jurisprudence may draw general rules to extract sentences from the detailed manuals/ Ø§ÙØ£Ø¯ÙØ© Ø§ÙØªÙØµÙÙÙØ© (al-Quran, al-Hadits), and absorbed important controls for weighting of evidence when they conflict, by those rules and disciplines can jurist extract sentences with ease and fluency and accuracy. As for jurisprudence this high standing and high status; it has its ancient Muslim scholars and newly collected discussing it, and accountability, and explained its features, we have facilitated this dificulty, and facilitated the consideration and understanding. This is knowledge of the differences in the jurisprudence of most detective, and most useful, to part ways with revised measurement areas, in terms of the measurement carried out perhaps the University branch, and this other than revising the areas, it is without these four pillars that cultivating illat and revise delete no entry for him in the Illat (Ø§ÙØ¹ÙÙØ©).That revision and course areas sounding and partitions in hand, the revision of the areas stated, this illat other than sounding Division, relates to the ills generated. To revise the impairments listed areas where the illat listed with descriptions of other, unrelated to the Illiyah (Ø¹ÙÙØ©/illat), either ØªØ®Ø±ÙØ Ø§ÙÙÙØ§Ø· is to extract the illat that no text at all, and this other than achieving regions it regards illat referred to in text or consensus by verifying its presence in section.So it would be easy to apply the law against problems occurred in the midst of us. how much does the opinion of scholars has been presented in various issues regarding this. tanqih al-manat.Â Keywords : Tanqih Al-Manath, Islamic Law, Ijtihad.